Strikes: Causes, Conduct and Consequences - Patmore, Greg (Labour / Le Travail, 1995)
The article reviews the book, "Strikes: Causes, Conduct and Consequences," by Douglas Blackmur.
Keywords: BLACKMUR; Douglas; BOOKS – Reviews; Nonfiction; STRIKES & lockouts; STRIKES: Causes; Conduct & Consequences (Book)